The Relationship between Psychosocial Burdens among Caregivers of patients with Renal Failure and their demographic attributes in Al-Diwaniyah Government - Hussein Hadi Hussein, Raad Karim Faraj (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A patient’s deteriorating medical state, the inability of families to finance therapy, medication, blood transfusions, or the hospitalization of patients may also be a genuine reason for this burden. There are several ways chronic renal failure affects the patient’s physical, psychological, functional, lifestyle, and independence status because of the disease’s long-term persistence and lengthy treatment procedure. Objective : Assess the overall Psychosocial Burden among caregivers for patients with renal failure, and find out the relationship between the overall psychosocial burden of caregiver and their demographic characteristics Methods: A descriptive correlation study design had been applied with the use of a non-probability convenience sample of (210) caregiver to identify the relationship between Psychosocial Burdens among Caregivers of Patients with Renal Failure and their demographic attributes in Al- Diwaniyah Government. The study instruments consist of the demographic information and Zarit Burden Interview (ZBI) scale that used to measure the degree of caregivers burdens during the caring of the patients with renal failure. The data were analyzed using (SPSS) version 20 application of statistical analysis system. The information was evenly distributed. Frequencies, Percentages, Mean and Standard Deviation, Pearson’s Correlation Coefficients, T-test (Independent t-test, and) To assess the significance difference between overall Caregivers burden. Results: The results of the study included that (74.8%) of the caregivers of patients with renal failure suffered from moderate to severe burden levels towards caring for their patients. The findings indicate that there is a statistically significant relationship between the psychosocial burden of the caregivers and their sociodemographic characteristics. The findings indicate that caregiver’ work, accommodation type, monthly income, and residency have an effect on their psychosocial burden level on the caregivers. Conclusions: Renal failure has negative effect on the caregiver for patient with renal failure. Psychosocial burdens for caregivers are influenced by caregivers’ demographic characteristics of the work of the caregiver, accommodation type, monthly income, and residency.